(untitled) (Balneo and PRM Research Journal, 2021)
Therapeutic plasma exchange (TPE) is an extracorporeal blood purification technique which removes large molecular weight particles, like autoantibodies, from plasma. Double filtration plasmapheresis (DFPP) is a newer technique in which plasma is not entirely removed, only the antibodies, using special filters. Myasthenia gravis (MG) is a well-known autoimmune disease characterized by antibodies against postsynaptic nicotinic acetylcholine receptors and fluctuating weakness, sometimes life-threatening. TPE is a therapeutic modality well established in MG with a positive recommendation based on strong consensus of class III evidence and in the category I of American society for apheresis. There are no adequate randomized control trial, but many cases report short-term benefit from plasma exchange in MG especially MGC. We analyzed the cases of neuroimmune disorders that were presented to our Emergency Care Unit between 2012-2020 and we concluded that good acceptance of procedure (TPE/DFPP) was observed in 72% of patients. TPE is cost-effective rapid therapy for myasthenic crisis and progressive myasthenia gravis. It reduces ICU stays and improves outcome.All in all recent studies show that the combination of rehabilitation and other forms of treatment, appropriately selected activities contribute to alleviating the symptoms of the disease, improving physical fitness, increasing muscle strength, and thus improving the quality of life.